Intellectual Capital, Firm Value, and Financial Performance - Aida Irsyahma; Nikmah Nikmah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
The ownership of intangible assets especially intellectual capital has becoming more important in this modern era where technology and knowledge have significant roles in company operating activities. The objective of this study is to examine the effect of intellectual capital on firm value and financial performance as intervening variable. The sample in this study is the banking sector listed in Indonesia Stock Exchange between 2011-2014 and 15 banks become samples in this study. The data was analyzed using the path analysis method with SPSS.The test result shows that intellectual capital has a positive effect on firm value, intellectual capital has a positive effect on financial performance, financial performance has a positive effect on firm value, and financial performance proved to intervene the relationship between intellectual capital and firm value.Keywords: Financial Performance, Firm Value, Intellectual Capital